Mobile miniature X-ray evaluation and pneumoconiosis: the role of the Clinica del Lavoro in Milan (1941-1948) - Porro, Alessandro; Lorusso, Lorenzo; Falconi, Bruno; Colombo, Andrea; Galimberti, Paolo Maria; Franchini, Antonia Francesca (La Medicina del Lavoro, 2018)
Since the end of the 19th century, X-rays have been used to detect lung diseases. In Italy, 207,096 miniature chest radiographs were taken from 1941 to 1948. Traditional radiographs gave better results, but miniature chest radiographs were useful for screening. Indeed, the development of mobile miniature chest radiography units resulted in an improvement in mass X-rays screening for the detection of penumoconiosis. These mobile miniature units were mounted on a bus chassis, a solution that allowed to easily reach workers. The authors analyze some models of X-ray wagon units used by the “Clinica del Lavoro” in Milan in the 1950s. From the point of view of medical museology, the preservation of these devices requires appropriate spaces.